Certain Trends in the Consumption of Wood in India - Mathur, R. S. (Indian Forester, 1975)
Some trends in the consumption of wood needed for a variety of uses likerailway sleepers, construtional timber, fuelwood, industrial wood, etc. are discussedin this paper.